Eclipsed sunray in the tonsil: mystery unfolded - Thangavel, Saranya; David, Charisha; Kuppusami, Magesh; Nalamate, Rajarajeswari; Phansalkar, Manjari; Kurien, Mary (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Actinomyces are saprophytic, filamentous branched bacteria, living as commensal organisms in the oral cavity. They become invasive when they gain access to the subcutaneous tissue, through a mucosal lesion. The common predisposing conditions are having dental caries, dental manipulations and maxillo facial trauma. Actinomycosis of the tonsil is usually related to obstructive tonsillar hypertrophy rather than recurrent tonsillitis. Since actinomyces is a normal inhabitant of the human body, it will be found in every anatomical site of the body. But tonsillar actinomycosis results from reduction of oxidation- reduction potential caused by pyogenic and anaerobic infections. Mucosal trauma plays a major role in the entry of the organisms. These organisms produce toxins and proteolytic enzymes to cause pathology within the tonsil. Dilated cystic spaces and neutrophilic infiltration are the unusual features highlighted in this report. Antibiotic therapy along with tonsillectomy is suggested as the preventive and curative treatment for tonsillar actinomycosis.